Peningkatan Hasil Belajar Luas Bangun Datar Melalui Penerapan Model Project-Based Learning di Sekolah Dasar - Putri, Nailil Faiqoh; Sukmanasa, Elly; Imaniah, Riksa Suci (Universitas Negeri Padang, 2023)
This study was motivated by the fact that students were more active in learning mathematics, but the activity was not mandatory and the methods used by teachers dominated lecture methods, leading to boredom and it influenced students' learning outcomes. Therefore, The purpose of this study is to achieve positive learning activities and learning outcomes can be improved by applying the Project-Based Learning (PjBL) model. This study used a Classroom Action Research (CAR) method of 29 students in her fourth grade from SDN Policy II Bogor City. The results of this study show a change in behaviour from 68% to 13% increase in Cycle I, an 81% increase in Cycle II, a skill increase from 68.4% to 11.6% in Cycle I, and an 80% increase in Cycle II increase. Cycle I learning outcomes increased by 41% and Cycle II by 38%. Therefore, The results of this study can be used as a reference for other researchers using Project-Based Learning to create innovative and meaningful learning.